An Empirical Analysis of the Effect of Poverty on Health Care Utilization in Kenya - Musyoka, Peter K.; Korir, Julius; Omolo, Jacob; Nzai, Charles C. (European Scientific Journal, ESJ, 2018)
Background Good health is a fundamental huma right, a valued asset, and a prerequisite for improved productivity. However, high poverty can lead to under utilization or lack of utilization of health care leading to poor health. Thus, poverty reduction and improvement of health care utilization are important in ensuring enjoyment of good health. Since 1982, poverty has remained above 40 per cent despite Kenya’s commitment to poverty reduction. Kenya’s health indicators have also not been impressive and health care utilization has remained low. Evidence shows that those who fell sick and reported lack of finances as the main reason for not seeking medical attention constituted 44 per cent, 38 per cent and 21.4 per cent in 2003, 2007 and 2013, respectively. These statistics point to poor health care utilization due to poverty. In Kenya, studies have concentrated on small segments of the population or parts of the country hence limiting generalization of the findings. Objective The objective of this paper was to determine the effect of poverty on health care utilization in Kenya. Method The study used a Negative Binomial Regression and the 2013 Kenya Household Expenditure and Utilization Survey dataset. The study also used Two Stage Residual Inclusion approach and a Control Function Approach to test and control for potential endogeneity and unobserved heterogeneity problems, respectively. Results The estimation results showed that reduction in poverty increased health care utilization. Other factors that had a positive and statistically significant effect on health care utilization were household size, early levels of education, and distance to the nearest health facility. Conclusion The study concludes that health care utilization is negatively affected by poverty other factors held constant. Thus, policies and strategies aimed at reducing poverty are needed. In particular the study recommends introduction of universal health care for all.